2000
DOI: 10.1007/s001140050700
|View full text |Cite
|
Sign up to set email alerts
|

Methane Ice Worms: Hesiocaeca methanicola Colonizing Fossil Fuel Reserves

Abstract: During a research cruise in July 1997 in the Gulf of Mexico we discovered a gas hydrate approximately 1 m thick and over 2 m in diameter which had recently breached the sea floor at a depth of 540 m. The hydrate surface visible from the submarine was considerably greater than that of any other reported hydrate. Two distinct color bands of hydrate were present in the same mound, and the entire exposed surface of the hydrate was infested (2500 individuals/m2) with 2 to 4 cm-long worms, since described as a new s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 12 publications
2
50
0
2
Order By: Relevance
“…Bathymodiolus mussels are foundation species that are responsible for modifying the environment at chemosynthetic habitats and provide hard substrate and shelter for many smaller morphospecies, as was observed during this study Levin et al, 2016). Interestingly, high abundances of amphipods on methane hydrate have not been seen before and suggests that the amphipods may occupy a similar trophic niche to the hesionid Hesiocaeca methanicola, which grazes on the abundant free-living chemoautotrophic bacteria on the hydrate (Figure 3; Fisher et al, 2000;Becker et al, 2013).…”
Section: Ecology Of the Communitiessupporting
confidence: 50%
“…Bathymodiolus mussels are foundation species that are responsible for modifying the environment at chemosynthetic habitats and provide hard substrate and shelter for many smaller morphospecies, as was observed during this study Levin et al, 2016). Interestingly, high abundances of amphipods on methane hydrate have not been seen before and suggests that the amphipods may occupy a similar trophic niche to the hesionid Hesiocaeca methanicola, which grazes on the abundant free-living chemoautotrophic bacteria on the hydrate (Figure 3; Fisher et al, 2000;Becker et al, 2013).…”
Section: Ecology Of the Communitiessupporting
confidence: 50%
“…Although these seafl oor gas hydrate deposits may constitute only a small percentage of the total amount of gas hydrate present in marine sediments, they represent the most accessible and best-studied deposits and are usually accompanied by complex fauna (e.g., Kulm et al, 1986;MacDonald et al, 1989;Fisher et al, 2000;Van Dover et al, 2003) that depend on a food chain based on symbiotic microorganisms similar to those found at hydrothermal vents.…”
Section: Focused High-flux Gas Hydrate Depositsmentioning
confidence: 99%
“…Olu et al 1997, Levin et al 2003. In the Gulf of Mexico, Fisher et al (2000) found the new polychaete species Hesiocaeca methanicola colonising the surface of gas hydrates. Several studies from chemosynthetically based ecosystems such as hydrothermal vents (Kamenev et al 1993), deep sea cold seeps (Shirayama & Ohta 1990), continental margin/shallow water cold seeps (Dando et al 1991, 1994, Jensen et al 1992, Buck & Barry 1998, coastal hydrocarbon seeps (Montagna & Spies 1985, Montagna et al 1987 and brine seeps at the East Flower Garden Bank, Gulf of Mexico (Jensen 1986, Powell et al 1986, showed that meiobenthic standing stocks benefit from the additional chemoautotrophic carbon input.…”
Section: Introductionmentioning
confidence: 99%